Cost-effectiveness of community health workers in tuberculosis control in Bangladesh - Islam, Md. Akramul; Wakai, Susumu; Ishikawa, Nobukatsu; Chowdhury, A.M.R.; Vaughan, J. Patrick (Bulletin of the World Health Organization, 2019)
Objective To compare the cost-effectiveness of the tuberculosis (TB) programme run by the Bangladesh Rural Advancement Committee (BRAC), which uses community health workers (CHWs), with that of the government TB programme which does not use CHWs. Methods TB control statistics and cost data for July 1996-June 1997 were collected from both government and BRAC thanas (subdistricts) in rural Bangladesh. To measure the cost per patient cured, total costs were divided by the total number of patients cured. Findings In the BRAC and government areas, respectively, a total of 186 and 185 TB patients were identified over one year, with cure rates among sputum-positive patients of 84% and 82%. However, the cost per patient cured was US$ 64 in the BRAC area compared to US$ 96 in the government area. Conclusion The government programme was 50% more expensive for similar outcomes. Although both the BRAC and government TB control programmes appeared to achieve satisfactory cure rates using DOTS (a five-point strategy), the involvement of CHWs was found to be more cost-effective in rural Bangladesh. With the same budget, the BRAC programme could cure three TB patients for every two in the government programme.